SYSTEMIC CLOSTRIDIOSIS DUE TO Clostridium perfringens INFECTION IN Equus asinus – CASE REPORT - LEMFERS, T. R.; VON AH, R. M. L.; GAGLIARDI, B.; PUCCI, L. R.; STANCIAR, B. P.; DÉRCOLI, T. E.; CALEFI, A. S. (Ars Veterinaria, 2022)
Clostridial infections, particularly clostridial myonecrosis, can be fulminant and fatal; they often arise without an obvious history of trauma. The majority of equine clostridial myonecrosis cases are associated with intramuscular injection. This paper presents the first report of clostridial myositis by C. perfringens in a donkey after an injection of flunixin meglumine on the neck, describing the clinical, necroscopic, and histopathological events. Bacterial isolation and biochemical tests confirmed the definitive diagnosis of C. perfringens.